Hydrogen generation from the reaction of Al pretreated in acidic or alkaline solution and water. (23rd October 2020) - Wang, N.; Xu, T.T.; Du, Y.H.; Li, L.; Chai, Y.J.
Abstract: Al and Al2 O3 film react with strong acid or alkaline solution, bring the extensive corrosion. To decrease the corrosion, Al is first pretreated with a small amount of HCl, NaOH, NaAlO2 and a mixture of NaAlO2 +Al(OH)3 in this work. Al pretreatment allows for the rapid removal of oxide film, shortens the induction time and ensures the initial Al–H2 O reaction rate. Typically, immersion of the pretreated Al by a mixture of NaAlO2 +Al(OH)3 into water, generates hydrogen rapidly without an induction time, and the average H2 generation rate reaches 5.5 mL min −1 . As the Al–H2 O reaction proceeds, the potential changes, which is similar to hydrogen evolution of pretreated Al in water. Hydrogen generated rapidly with the consecutive addition of Al, and the initial hydrogen generation rate reaches ~37 mL min −1 . Therefore, Al pretreatment by a mixed alkaline solution is an effective method to accelerate hydrogen generation for the first cycle. Rapid and consecutive hydrogen generation by the Al–H2 O reaction could provide on-demand and high-purity hydrogen, meet some equipment requirements and promote the competition in renewable-energy sources. Graphical abstract: Image 1 Highlights: Al pretreatment can accelerate oxide-film removal and favors the subsequent Al–H2 O reaction. Al Pretreated by a mixture of NaAlO2 +Al(OH)3 generates hydrogen rapidly without an induction time. Hydrogen generated rapidly with the consecutive addition of Al.